Detection rate of pulmonary tuberculosis by direct and concentrated microscopy techniques with Lowenstein-Jensen Culture as standard: South-South Nigeria Scenario - Ekom Ndifreke Edem; Anthony Nathaniel Umo; Olajide Joseph Akinjogunla; Adel AE Elahmar; David Arome (Open Journal of Bacteriology - Peertechz Publications, 2022)
Objective: This study seeks to identify a more sensitive smear microscopy method for the detection of Mycobacterium tuberculosis in low-resource centers.  Materials and methods: One hundred and forty sputum specimens were collected and direct smears were prepared as the specimen was submitted. The specimens were afterward digested/decontaminated using the modified Petroff's method. Both smear methods were stained by the Ziehl-Neelsen technique and examined. All specimens (direct and concentrated) were cultured on a Lowenstein-Jensen medium and results were considered the gold standard to calculate sensitivity.  Results: Out of 140 specimens, 27 (19%) and 34 (24%) were positive by direct and concentrated methods respectively. The number of culture positives by the direct and concentrated method was 26 (19%) and 31(22%) respectively. The sensitivity of direct and concentrated methods was 92.3% and 100% respectively. The negative culture and contamination rate was minimum with the concentrated method. The diagnostic accuracy of direct and concentrated methods was 88.6% and 97.1%.  Conclusion: In summary, results showed concentrated techniques were able to detect more true positive Mycobacterium tuberculosis than the direct smear method. Therefore, the study region with AFB smear microscopy can utilize the concentrated smear method for AFB smear microscopy to improve the case-finding strategy.